Trumpeter of krakow eaudiobook - Kelly, Eric (Recorded Books Inc., 1999)
It is late July in 1461 when young Joseph Charnetski and his family arrive in the great city of Krakow, with its glorious church towers and lively marketplace. The Charnetskis have come to Krakow to seek refuge with their relatives. What they find is more danger and adventure than a simple farm boy like Joseph could ever have imagined. First, a menacing stranger tries to take their pumpkin at sword point. Then a beautiful girl and her black-robed uncle befriend Joseph. Soon he and his family are caught up in the plots of alchemists, hypnotists, and a dark messenger of evil. This distinguished contribution to children's literature carries listeners to a medieval Poland shimmering with folklore and fantasy. Rich in language and detail, it is a classic adventure story that begs to be read aloud. With narrator Ron Keith's expressive, resonant voice, the effect is as stirring as the haunting hymn the trumpeter plays from the church tower.